Cooccurrence of Talon's Cusp with Dens Invaginatus in the Maxillary Lateral Incisor: A Case Report with Review of Literature - Snehashish Ghosh; Safal Dhungel; Bhawana Subedi; Subi Pradhan (Hindawi Limited, 2022)
Morphogenic developmental anomalies are common in maxillary lateral incisors, but simultaneous occurrence of two developmental anomalies in a single tooth is relatively uncommon. In this case report, we present a case of cooccurrence of the talon's cusp with dens invaginatus in the left lateral incisor tooth. Early diagnosis and prompt treatment of such cases are important to prevent any untoward consequences.